THE IMPLEMENTATION AND IMPLICATIONS OF THE ELECTRONIC AND INFORMATION TRANSACTIONS LAW AGAINST CYBER BULLYING BY SUBSQUENT OF THE CONSTITUTIONAL COURT DECISION RELATED TO THE FREEDOM OF SPEECH - Gumbira, Seno Wibowo; .Daryono, Daryono; Nurhayati, Ratna (Faculty of Law, Universitas Sebelas Maret, 2017)
This article aimed to observe the criminal provisions both in the Formulation of the EIT ACT 2008 along with the verdict of the judicial review of the Constitutional Court Number 50/PUU-VI/2008 as well as the EIT ACT 2016 especially in strictly contained in article 27 along with the norm of the criminal sanctions contained in Article 45 can still be said to be a ”Rubber Articles”, so it requires linguist and religious leaders in order to get a description or explanation of a remark or action in conflict with religious values and modesty as well as decency in public life. The Guarantee Of Freedom Of Speech. Then when viewed from the highest norm of the 1945 Constitution to the level of the law that is Article